Authentication of Processed Beef Sausage Products Using Chemometric Analysis Based on FTIR Spectrophotometry Data - Sonny Widiarto; Raisha Fauziyah; Triana Puji Astari; Ni Luh Gede Ratna Juliasih; Sutopo Hadi; La Zakaria; Irwan Saputra (Jurnal Kimia Sains dan Aplikasi, 2025)
This study aims to detect chicken meat contamination in beef sausage products distributed in Bandar Lampung City, Lampung Province. The selection of chicken and beef for this research is based on economic factors, as the higher price of beef compared to chicken drives the adulteration of meat products. The sausage fat was obtained using the Soxhlet extraction method with n-hexane solvent. Subsequently, the sausage fat extract was analyzed using FTIR (Fourier Transform Infrared) spectrophotometry to obtain infrared spectral data. This data was then analyzed using chemometric methods PCA (Principal Component Analysis) and PLS (Partial Least Squares). The PCA analysis results indicated that commercial sausages (AP, BP, CP, DP, and EP) and pure beef sausages showed closely clustered samples, suggesting similar physical and chemical properties with pure beef sausages. The PLS calibration set analysis yielded a model with a coefficient of determination (R2) value of 0.970409 and a root mean square error of calibration (RMSEC) parameter value of 0.09%, while the PLS validation set analysis produced a model with a coefficient of determination (R2) value of 0.963486 and a root mean square error of prediction (RMSEP) parameter value of 0.13%. Based on the PLS model predictions, it was determined that the percentage of chicken meat mixed in beef sausages circulating in the market ranged from 0.0281% to 0.1106%. This indicates a small but notable adulteration in beef sausages with chicken meat.